Speculating in zero-value assets: The greater fool game experiment - Armando Holzknecht; Jürgen Huber; Michael Kirchler; Tibor Neugebauer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
In a pre-registered laboratory asset market study, we investigate dynamics of asset markets with zero (or close to zero) fundamental values. We introduce the "greater fool asset market game" with a zero-value token, whose price doubles in each period. We design several treatments, which differ in terms of whether the fundamental value is zero for sure, and whether the rather low probability of non-zero fundamentals is known (Risk) or not (Ambiguity). We find that prices in markets with zero fundamental value are clearly above zero. Furthermore, we report that prices in treatment Ambiguity are substantially higher than those in the baseline and in treatment Risk. Finally, we show that beliefs regarding the asset's value and others' participation explain individual market participation.
Keywords: C91; C92; G12; G41; 330; speculative bubbles; greater fool; behavioral economics; experimental finance